1993
DOI: 10.1111/j.1365-2184.1993.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in expression of genes used for normalization of Northern blots after induction of cell proliferation

Abstract: Quantitative knowledge of gene expression can provide valuable information for understanding the action of chemicals that alter cell proliferation and cancer. Accurate quantification of mRNA levels requires the normalization of the gene of interest to a gene with transcriptional levels that do not vary through the cell cycle or with a particular treatment. Changes in expression were examined in proliferating or non-proliferating rat liver for three constitutively expressed 'housekeeping' genes commonly used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 17 publications
(1 reference statement)
1
29
0
2
Order By: Relevance
“…21 However, the use of housekeeping genes as standards of reference for normalization, and the use of actin in particular, has recently been questioned. 36,37 Therefore, synaptophysin was employed in the present study as a reference standard and as an alternative measure of synaptic protein expression, but was not used to normalize the synapsin measurements. Actin was not measured in the present study as it was not sufficiently separated from synapsin to allow for measurement on the same blots.…”
Section: Western Blotsmentioning
confidence: 99%
“…21 However, the use of housekeeping genes as standards of reference for normalization, and the use of actin in particular, has recently been questioned. 36,37 Therefore, synaptophysin was employed in the present study as a reference standard and as an alternative measure of synaptic protein expression, but was not used to normalize the synapsin measurements. Actin was not measured in the present study as it was not sufficiently separated from synapsin to allow for measurement on the same blots.…”
Section: Western Blotsmentioning
confidence: 99%
“…The synthesis of those molecules is often considered as being very few fluctuating in comparison to that of others and, by their commonplace use, are considered in many laboratories as constant and secure. But numerous studies showed that even these genes see their expression even highly does vary in given situations (Huitorel and Pantaloni, 1985;Zhang and Snyder, 1992;Goldsworthy et al, 1993;Hobbs et al, 1993;Bhatia et al, 1994;Bereta and Bereta, 1995;Lemay et al, 1996;Chang et al, 1998). This may partly be explained by the fact that housekeeping proteins are not only implicated in the basal cell metabolism but also participate in other functions (Petersen et al, 1990;Singh and Green, 1993;Ishitani et al, 1996).…”
mentioning
confidence: 99%
“…The most often considered and used housekeeping genes are those for albumin (for hepatocytes) (Goldsworthy et al, 1993), b-, g-actins (Choi et al, 1991;Wei et al, 1997), cyclophilin (Bjarnason et al, 1998;Jaschke et al, 1998), G3PDH (Petersen et al, 1990;Tang et al, 1996), a-, b-tubulins (Choi et al, 1991;Serels et al, 1998), hypoxantine phosphoribosyltransferase (HRPT) (Marten et al, 1994;Foss et al, 1998), L32 for other cell types (Lemay et al, 1996;Wu et al, 1999) or 18S, 28S rRNA (Finnegan et al, 1993;Bhatia et al, 1994). The essential functions of these molecules are variable (Table 1).…”
mentioning
confidence: 99%
“…Animals treated by carbon tetrachloride or undergoing partial hepatectomy show an increase in aspartate transaminase and ALT plasma activity, with a maximum at 6 hours. 27 Because SAM prevented liver gene expression changes induced by TAM, this effect being blocked by BSO, we decided to see if similar results assaying the ALT serum activity, a parameter of liver injury, were obtained. TAM-treated animals had increases in the serum ALT activity with a peak around FIG.…”
Section: Analysis Of the Serum Alt Activity As A Marker Of Hepatotoximentioning
confidence: 99%